Determinan Finansial Distress Pada Perusahaan Sektor Consumer Cyclicals Yang Terdaftar Di Bursa Efek Indonesia - Mohamad Zulman Hakim; Aprilliani Tri Wiyanti, Imam Hidayat; Januar Eky Pambudi; Dirvi Surya Abbas; Sustari Alamsyah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of liquidity, profitability, the ratio of activity to financial distress. The population in this study is all Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange for the 2019- 2021 period. The sampling technique uses purposive sampling and obtained the company or 66 samples. The analysis technique used in this study is purposive sampling analysis. Research results; liquidity,profitability and activity ratio have no effect on financial distress.